2009
DOI: 10.1038/emboj.2009.151
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of key features of the p63-null epithelial phenotype by inactivation of Ink4a and Arf

Abstract: Mice lacking p63 cannot form skin, exhibit craniofacial and skeletal defects, and die soon after birth. The p63 gene regulates a complex network of target genes, and disruption of p63 has been shown to affect the maintenance of epithelial stem cells, the differentiation of keratinocytes, and the preservation of the adhesive properties of stratified epithelium. Here, we show that inactivation of p63 in mice is accompanied by aberrantly increased expression of the Ink4a and Arf tumour suppressor genes. In turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 48 publications
(106 reference statements)
4
74
1
Order By: Relevance
“…It was shown that the efficiency of reprogramming depends on normal cell proliferation. 13,28 Consistent with the reported hypoproliferation of p63 À / À keratinocytes, 39 we observed that p63 À / À MEFs proliferate slower than their WT counterparts (Figures 3a and c). Thus, we tested whether improving proliferation of p63 À / À MEFs would restore their OSK reprogramming efficiency.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It was shown that the efficiency of reprogramming depends on normal cell proliferation. 13,28 Consistent with the reported hypoproliferation of p63 À / À keratinocytes, 39 we observed that p63 À / À MEFs proliferate slower than their WT counterparts (Figures 3a and c). Thus, we tested whether improving proliferation of p63 À / À MEFs would restore their OSK reprogramming efficiency.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, the tumor suppressors p19-Arf and p16-Ink4A, which are known reprogramming barriers in mouse and human fibroblasts, 23,24 were shown to partially mediate skin and limb defects of p63 À / À mice. 39 However, p19 and p16 are again unchanged in p63 À / À MEFs before and during reprogramming (Figure 3e). Thus, the defective OSK and OS reprogramming of p63 À / À MEFs cannot be explained by upregulation of likely reprogramming barriers in this context.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As a transcriptional repressor, p63 maintains proliferation of basal epidermal keratinocytes by directly repressing expression of antiproliferative target genes, including 14-3-3s, p16/Ink4a, p19/Arf, p21, and PTEN (Westfall et al 2003;Watt et al 2008;Su et al 2009a;Leonard et al 2011;Ferone et al 2012). In addition to cellcycle-associated genes, p63 inhibits the expression of nonkeratinocyte genes (i.e., mesodermal genes), as well as a number of other genes such as distinct components of the Notch (Notch1, Hes1) and bone morphogenetic protein (BMP) signaling pathways (Smad7) in epidermal keratinocytes (Nguyen et al 2006;De Rosa et al 2009;Shalom-Feuerstein et al 2011).…”
Section: Va Botchkarev and Er Floresmentioning
confidence: 99%
“…DNp63a is an oncogene that suppresses the activity of the Ink 4A /ARF locus [10] and opposes the tumor suppressive effects of cellular senescence [11,12] suggesting a role in oncogenic initiation [13]. TP63 is amplified at the genomic level in 9.7% of head and neck squamous cell carcinomas, 12.9% of serous ovarian carcinomas, 23% of squamous cervical carcinomas and 28.5% of lung squamous cell carcinomas (http://cbioportal.…”
Section: Introductionmentioning
confidence: 99%